2002
DOI: 10.1076/clin.16.3.341.13852
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Coping, Cognitive Dysfunction and Depression in Multiple Sclerosis

Abstract: Given its relatively high prevalence, one possible source of stress for patients with multiple sclerosis (MS) is cognitive dysfunction. The authors' study was guided by a new theoretical model suggesting that cognitive dysfunction in MS may be most likely to lead to depression when patients use high levels of avoidance coping and/or low levels of active coping. To test this model, 55 patients with definite MS were administered a neuropsychological battery and measures of depression and coping. Consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 40 publications
7
91
2
4
Order By: Relevance
“…Tests that emphasized episodic memory and processing speed were most sensitive and logistic regression models revealed that tests emphasizing processing speed, verbal memory, and executive function were predictive of vocational status. Depression, was not significantly related to cognitive performance, consistent with some previous findings (Benedict et al, 2002a) but not others (Arnett et al, 1999;Arnett et al, 2002). Patients were gleaned from a number of different sources as documented prior to testing.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Tests that emphasized episodic memory and processing speed were most sensitive and logistic regression models revealed that tests emphasizing processing speed, verbal memory, and executive function were predictive of vocational status. Depression, was not significantly related to cognitive performance, consistent with some previous findings (Benedict et al, 2002a) but not others (Arnett et al, 1999;Arnett et al, 2002). Patients were gleaned from a number of different sources as documented prior to testing.…”
Section: Introductionsupporting
confidence: 85%
“…In general, correlations between NP testing and depression are modest, sometimes significant (e.g., Arnett et al, 1999;Arnett et al, 2002), sometimes not (e.g., Benedict et al, 2002a). Our analysis provided an opportunity to learn if such variation is related to recruitment context.…”
Section: Discussionmentioning
confidence: 91%
“…Depression of the parents was assessed by the short form of the Beck Depression Inventory (BDI), which is a valid and reliable measure of depressive symptoms in both depressed and medical populations (Beck et al 1961(Beck et al , 1988 and has been widely used in MS-patients, (e.g., Arnett et al 2002;Feinstein and Feinstein 2001;Landro et al 2004). ''Somatic'' BDI items might be valid as depression indicators for at least some MS patients (Aikens et al 1997).…”
Section: Demographicsmentioning
confidence: 99%
“…In particular, Arnett and colleagues 13 reported that the relationship between cognitive impairment and depression was higher among those who were not using active coping strategies. To the extent that health-promotion activities might be considered an active coping mechanism for people with MS, we might expect a positive relationship between What is the evidence for construct and criterion validity of the PROMIS cognitive scales as measures of perceived cognitive functioning in people with MS?…”
mentioning
confidence: 99%